PENGEMBANGAN MEDIA PEMBELAJARAN SMARTBOX UNTUK MENINGKATKAN RESILIENCE BELAJAR MATEMATIKS PESERTA DIDIK PADA MATERI PENJUMLAHAN DAN PENGURANGAN KELAS 1 SDN SENDANGHARJO 3 - Siti Oktavia Etik Candrawati; Wendri Wiratsiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop innovative game-based learning media called smartbox, to improve the resilience of learning mathematics in grade 1 elementary school students on addition and subtraction materials. Using a research approach and the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the product is tested for validity, practicality, and effectiveness. The results show that the smart box media is valid in terms of content and design, practical in use in the classroom, and effective in improving resilience indicators such as self-confidence, perseverance, and the ability to face difficulties in learning mathematics.